Mosquito Larvae Inspection in Sangaji Village, Ternate City - Nurul Mahzidal Umasangaji; Wa Naziroh Salfiani; Talha Safrudin; Nurul Syafitri Nanggung; Nava Baswati Umasangaji; Sofia A. Larahim; Nurfaida Lapatilaiya; Tutik Lestari (BIOSAINSTEK, 2025)
The unfavorable climate conditions in recent weeks have become a breeding ground for mosquito larvae, which can lead to a public health issue known as Dengue Hemorrhagic Fever (DHF). If not addressed properly, it can lead to extraordinary incidents and even result in death. The prevention and control measures for DBD have not been adequately addressed, therefore requiring community involvement in efforts to eradicate mosquito breeding sites in residential areas. Method: Observation by visiting residents' homes to conduct mosquito larvae inspections, distribute larvicides (Abate powder), and provide direct education to household members about dengue fever, as well as distribute leaflets about dengue fever. Results: Out of the 27 houses visited, it was found that 12 houses (92.3%) had mosquito larvae, while 9 houses (64.3%) did not have mosquito larvae in RT 014/RW 005. In RT 003/RW 001, 1 house (7.7%) had mosquito larvae, while the remaining 5 houses (35.7%) did not have mosquito larvae. There are various types of water storage containers where mosquito larvae were found, including bathtubs, buckets, dispensers, drums, and flower vases.